Mechanisms of Propolis Ethanol Extracts to Alleviate Sarcopenia based on Network Pharmacology and Experimental Validation - Tian, Songhao; Chen, Tao; Song, Congying; Guo, Hongru; Jiang, Conglin; Feng, Wei (Combinatorial Chemistry & High Throughput Screening, 2025)
<span class=
Keywords: PEE